2014
DOI: 10.1103/physrevb.90.155204
|View full text |Cite
|
Sign up to set email alerts
|

Optoelectronic properties ofTa3N5: A joint theoretical and experimental study

Abstract: A joint theoretical and experimental study of the opto-electronic properties of Ta3N5 was conducted by means of ab initio calculations and ellipsometry measurements. Previous experimental work on Ta3N5 has not been conclusive regarding the direct or indirect nature of light absorption. Our work found excellent agreement between the optical spectrum computed using the BetheSalpeter Equation and the measured one, with two prominent features occurring at 2.1 and 2.5 eV assigned to direct transitions between N and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 54 publications
5
44
0
Order By: Relevance
“…5(a)) with a band gap energy of 3.1 eV. The lowest-energy band gap of this material originates from the direct O 2p 6 -Bi 6p 0 orbital transitions. For Bi 4 Ti 3 O 12 , the electronic analysis reveals that valence-band states in a wide energy range below the Fermi level are dominated by O 2p orbitals with negligible contributions from Bi 6s orbitals, whereas the conduction-band states primarily consist of empty Ti 3d orbitals (Fig.…”
Section: A Structural Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…5(a)) with a band gap energy of 3.1 eV. The lowest-energy band gap of this material originates from the direct O 2p 6 -Bi 6p 0 orbital transitions. For Bi 4 Ti 3 O 12 , the electronic analysis reveals that valence-band states in a wide energy range below the Fermi level are dominated by O 2p orbitals with negligible contributions from Bi 6s orbitals, whereas the conduction-band states primarily consist of empty Ti 3d orbitals (Fig.…”
Section: A Structural Propertiesmentioning
confidence: 99%
“…[1][2][3][4][5] This is particularly relevant in the case of semiconductor materials for solar applications, [6][7][8][9][10] where the capability of the semiconductor to use effectively solar light depends on combination of a series of properties. 2 Thus, the efforts devoted to the accurate theoretical and experimental characterization of a large variety of semiconductor materials aimed to elucidate fundamental properties, such as band gap, optical absorption coefficient, dielectric constant, and charge carrier effective masses.…”
Section: Introductionmentioning
confidence: 99%
“…We considered (i) uniaxial strain along a, b and c directions (see band minimum (CBM) located at Y point. 8 We found that hydrostatic strains between −1.5% and 1.5% induce small changes in the band gap, less than 1.5% (see Fig. S5 (c)), while uniaxial strain along the b direction induces changes up 5.6% (Fig.…”
Section: Resultsmentioning
confidence: 73%
“…3 However, recent experiments have reported low photocurrent and poor overall performance of Ta 3 N 5 photoanodes for water oxidation, 4,5 which is likely caused by poor charge transport properties [6][7][8] as well as by rapid photodegradation of the samples in water.…”
Section: Introductionmentioning
confidence: 99%
“…This observation agrees well with similar effective masses for electrons and holes theoretically estimated for Ta3N5. 57,58 The ultrafast quenching of holes at the Ta3N5 phase is consistent with its poor OER performance (provided that trapped holes are not energetically suitable to promote OER after trapping). From THz characterization, we cannot conclude whether the hole traps are present in the surface or in the bulk phase.…”
Section: Figure 1 (A) Time Courses Of Photocatalytic Oermentioning
confidence: 77%